Sistem Pendukung Keputusan Pemberian Reward Kepada Kurir di Jakarta Utara Menggunakan Profile Matching - Randy Teguh Waluya Nugraha; Budi Arifitama; Yaddarabullah Yaddarabullah (Politeknik Negeri Batam, 2021)
Courier employees in an expedition company are an important asset for the company. Each Courier has a daily productivity performance to aim with a perfect score (100%) to gain a reward. However, an assessment based only on productivity performance cause problems, where it is impossible to achieve a perfect productivity score to get a reward. This research focus to improve the rewarding system using a decision support system by adding other aspects than productivity which is the behavioral aspect. Absentee, successful delivery, cash on delivery, status update, attendance, and lateness are the behavioral aspect criteria used. Profile Matching method is conducted to compare employee profiles with the standard values and calculate its GAP. The smaller the GAP, the greater the weight results for the best alternative solution. The results, from 150 employees, 5 employees were selected as the best employees and granted rewards with the highest position scored 4,733, second scored 4,725, third scored 4,7234, fourth scored 4,722, and fifth scored 4,721. Profile matching has proven to be excellent as a method for a decision support system to reward employees based on ranking.